The effect of online learning setting on motivation to learn EFL among students of child education profession - Zrinka Fiser; Luka Pongracic (Knowledge Management & E-Learning: An International Journal)
Motivation to learn a second and foreign language has been researched for several decades, initially employing the socio-educational model, and later the multi-dimensional model of motivational factors. The authors investigated the motivation of 279 non-English major students at University of Slavonski Brod (UNISB) in Croatia in learning English as a foreign language, with an aim to distinguish how an online learning experience caused by the COVID-19 pandemic shaped their extrinsic and intrinsic motives. They applied the five-component motivational system, consisting of motives related to future self-guides, instrumentality driven motives and previous learning experience. The analysis of the collected data showed that the intended effort to learn a target language, which gained more relevance as a motivational component than before COVID-19, varied between pre-pandemic and post-pandemic research findings. The motivational dimension of online learning showed no change in the importance of motivation connected to participants’ feeling of duties, obligations, and responsibilities, but it did show a stronger correlation with motives that support learning. Further analysis also revealed a significant positive effect of online learning during secondary schooling with both instrumentality driven motives, and online learning during tertiary education with all the motivational dimensions except intended effort.